(untitled) (Journal of Pakistan Orthopaedic Association, 2021)
Objectives: To compare the radiological and functional outcomes of lateral, medial and posterior approaches for open reduction and k wire fixation in children with type III supracondylar fractures of the humerus. Methods: We conducted this retrospective Cohort study in Orthopedic department Dr. Ruth K M Pfau Civil Hospital Karachi. All children with type III supracondylar fracture of the humerus fulfilling the inclusion criteria operated in time period extending from 3rd January 2018 to 3rd December 2020 and with minimum one year follow up were included. The clinical records were reviewed for surgical approaches and children with lateral approach(LA),medial approach(MA) and posterior approach(PA) were asked for follow up visit. Radiological outcome was assessed by measuring Shaft Condylar Angle(SCA) and Baumann angle. Flynn’s criteria was used for functional outcome in all children and results were categorized into Excellent, Good, Fair(satisfactory) and Poor(unsatisfactory). Results of lateral, medial and posterior approach were compared and P value was calculated with Chi-Square test and Kruskal-Wallis test (P value <0.05 significant). Results: The total number of children in our study were 90. Each LA, MA and PA had 30 children each. Mean age of children in LA was 8.54 ± 4.5 years, MA 7.21 ± 3.5 years and PA 8.1 ± 6.1 years. Mean Shaft Condylar Angle was 42.2±7.1o, 42.5±3.2o and 41.3±2.7o in LA,MA and PA respectively(P> 0.05). Mean Bauman angle was 19.4±4.0o in LA, 20.3±6.3o in MA and 21.6±3.1o in PA (P> 0.05). Excellent outcome was noted in 22(73.33%),17(56.66%) and 15(50%) in LA,MA and PA respectively. ( P> 0.05)Good outcome was noted in 8(26.66%) children in LA, 13(43.33%) in MA and 15(50%) in PA.(P >0.05) Conclusion: Lateral approach for supracondylar fracture yielded better radiological and functional outcome than medial and posterior approach in our patients. The difference was however not statistically significant.